Description of the female of Parapsyche cardis Ross (Hydropsychidae: Arctopsychinae) and a revised key to the genera of Hydropsychidae (Trichoptera: Annulipalpia) of the southeastern United States, using wing characters - Stocks, Ian C. (Zootaxa, 2011)
The female of Parapsyche cardis Ross is described and the female of Parapsyche apicalis (Banks) is redescribed and illustrated. A key is provided to the genera of Hydropsychidae of the southeastern United States, based primarily on wing characters.